Budd-Chiari syndrome due to giant hydatid cyst: a case report and brief - Akbulut, S; Yilmaz, M; Kahraman, A; Yilmaz, S (2013)
Budd-Chiari syndrome is an uncommon disorder characterized by the thrombotic or non-thrombotic obstruction of hepatic venous outflow anywhere along the venous course from the hepatic venules to the junction of the inferior vena cava and the right atrium. The etiology of Budd-Chiari syndrome is classified as primary, attributable to intrinsic intraluminal thrombosis or the development of venous webs; or secondary, caused by intraluminal invasion by a parasite or malignant tumor or extraluminal compression by an abscess, solid tumor, or cyst, such as a hydatid cyst. In this study, we present a case of a giant hydatid cyst manifesting Budd-Chiari syndrome symptoms and signs by compressing the inferior vena cava and hepatic veins. In brief, the case demonstrates that hydatid disease should be considered in the differential diagnosis of Budd-Chiari Syndrome in areas such as Turkey, where hydatid disease is endemic. C1 [Akbulut, Sami; Yilmaz, Mehmet; Yilmaz, Sezai] Inonu Univ, Fac Med, Dept Surg, Div Liver Transplantat, TR-44280 Malatya, Turkey. [Kahraman, Aysegul] Inonu Univ, Fac Med, Dept Radiol, TR-44280 Malatya, Turkey.